To Drive Is Human. - Miller, Isaac; Garcia, Ephrahim; Campbell, Mark (Computer (00189162), 2006)
The article presents the perspectives of various researchers at Cornell University on the issues the Defense Advanced Research Projects Agency Grand Challenge competitors encountered in creating a humanlike driver in the U.S. They divided the driving problem to be matched by computers to three basic tasks, localization, sensing, and path planning. One issue is how human differs from the operation of autonomous vehicles, the main distinction between a human driver and an autonomous driving system. Another is the driving domain knowledge possessed by both human drivers and autonomous driving systems and how they select a driving path.